Description of a new genus and species, Portentus marschneri (Coleoptera: Anthribidae), from Penang National Park, Malaysia - Trýzna, Miloš; Baňař, Petr (Zootaxa, 2021)
A new genus and species, Portentus marschneri Trýzna & Baňař gen. nov. & sp. nov. (Anthribidae: Anthribinae: Phloeophilini), from Penang National Park, Malaysia is described. Male genitalia are studied and illustrated and colour photographs are provided. A key is provided to distinguish Portentus from similar Palaearctic and Oriental genera of the tribe Phloeophilini: Phloeophilus Schoenherr, 1833, Bothrus Wolfrum, 1956, and Morimotanthribus Senoh & Trýzna, 2006.